Research on Regional low-carbon development path based on LEAP model: Taking the Lin-gang Special Area as an example - Hongbo Ren; Qiong Wu; Weiguo He; Wei Wang; Xiao Luo; Qifen Li; Zipei Jiang (Energy Reports, 2022)
Based on the economic and social development, as well as the resource factor endowment in the Lin-gang Special Area, the LEAP model is employed as the research tool to analyze the energy consumption and carbon emissions from 2021 to 2060 under different scenarios. The results show that under the baseline scenario, the carbon emission in the special area basically enters the platform period after 2035; Under the low-carbon scenario, the carbon peak can be achieved in 2035, but the subsequent decline is relatively slow; Under the enhanced low-carbon scenario, the special area can reach the peak synchronously with the national goal in 2030 and basically achieve carbon neutrality in 2060. In addition, the contribution analysis of emission reduction for different policy measures shows that the contribution of clean energy substitution is the largest, followed by energy efficiency improvement and electrification.